Pre-registration: Passenger Density on Stockholm Subway Platforms With and Without Blue-Light Exposure: A Quasi-experimental Observational Study - Berglund, Danielle; Hadlaczky, Gergö; Alvarsson-Hjort, Jesper (Karolinska Institutet, 2026)
This dataset contains observational count data on passenger presence on subway platforms in the Stockholm metro system, collected as part of a quasi-experimental field study examining behavioural responses to blue LED lighting, BLED. Data were collected at four platforms across three subway stations between September 2025 and April 2026. Two platforms were equipped with blue LED luminaires and two served as non-exposed control platforms.

Note: For the purpose of preregistration and documentation, the files provided at this stage contain simulated data only. These simulated files mirror the structure, variables, formats, and temporal alignment of the real data that will be analysed once data collection is complete.

The core data consist of time stamped detections from the station camera system, provided as event level logs that is aggregated to minute-by-minute counts. For each platform, two zones were defined within the camera system, an exposure zone located at the platform end where trains enter the station and an adjacent reference zone with standard lighting. Automated video analytics identified human presence within these zones and recorded detections over time. The dataset does not include images, video recordings, or individual level tracking, only anonymised numerical event counts that can be summarised to passenger density measures. Lighting conditions at the exposed platforms alternated between BLED switched on and switched off, primarily in two-week periods with one four-week period, allowing within platform and between platform comparisons over time. Each camera based observation is time stamped and linked to station, platform, zone, experimental condition, and period identifiers.

The dataset also includes aggregated station passage data derived from ticket gate systems at the same stations. These data describe the number of passengers entering and exiting each station at minute resolution and serve as indicators of overall station usage that can be aligned temporally with the camera data to control for variation in passenger volume unrelated to lighting conditions.

To account for ambient lighting conditions, the dataset further includes environmental data from an outdoor reference station. This file contains time stamped measurements of solar irradiance and is used as a control variable for changes in natural light exposure over the study period.

The data material is provided as structured tabular files corresponding to these three sources, camera detections, station passage counts, and outdoor sun exposure. The files are linked through shared timestamps and station identifiers and can be read using standard statistical software. No proprietary software is required, and the original analyses were conducted in R, although reuse is not restricted to any specific software environment.

Datamaterialet innehåller observationsdata för resenärers närvaro på fyra tunnelbaneplattformar i Stockholm och har samlats in inom ramen för en kvasi-experimentell fältstudie av beteendemässiga effekter av blå LED-belysning, BLED. Datainsamlingen genomfördes vid plattformarna på tre tunnelbanestationer under perioden september 2025 till april 2026. Två plattformar var utrustade med blå LED-armaturer och två fungerade som kontrollplattformar.

Obs! Denna förhandsregistrering består av filer som endast innehåller simulerade data. De simulerade filerna återspeglar struktur, variabler, format och tidsmässiga samordningen hos de verkliga data som kommer att analyseras när datainsamlingen är avslutad.

Kärnan i datamaterialet utgörs av tidsstämplade händelseloggar från stationernas kamerasystem, tillhandahållna minutvis räknedata som sedan aggregeras. På varje plattform definierades två zoner i kamerasystemet, en exponeringszon placerad vid den plattformsände där tågen anländer till stationen samt en intilliggande referenszon med ordinarie belysning. Automatiserad videoanalys identifierade personer i dessa zoner över tid. Datamaterialet innehåller inga bilder, videoinspelningar eller individbaserad spårning, utan enbart anonymiserade numeriska händelser som till ett index för resenärstäthet.

På de exponerade plattformarna växlade belysningen mellan att B-LED var påslagen och avstängd, huvudsakligen i tvåveckorsperioder samt en fyraveckorsperiod. Detta möjliggör jämförelser både inom samma plattform över tid och mellan exponerade plattformar och kontrollplattformar. Varje kamerabaserad observation är tidsstämplad och kopplad till station, plattform, zon, experimentellt tillstånd samt period.

Datamaterialet omfattar även aggregerade passageuppgifter från stationernas spärrsystem. Dessa data redovisar antal resenärer som passerar in och ut ur stationerna med minutupplösning och används som indikatorer på den övergripande resenärsvolymen. Passageuppgifterna kan tidsmässigt synkroniseras med kameradatan för att kontrollera för variationer i resande som inte är relaterade till belysningsförhållandena.

För att kontrollera för variationer i omgivande ljusförhållanden ingår även miljödata från en extern referensstation. Denna fil innehåller tidsstämplade mätningar av solinstrålning och används för att beskriva förändringar i naturligt ljus över studieperioden.

Datamaterialet tillhandahålls som .csv filer en för vardera datakälla, kameradetektioner, passageuppgifter och utomhusdata för solinstrålning. Filerna kan kopplas samman via gemensamma tidsstämplar och stationsidentifierare och kan läsas med vanliga statistikprogram. Ingen licensierad eller specialiserad programvara krävs. De ursprungliga analyserna genomfördes i programmeringsspråket R, men datamaterialet är inte bundet till någon specifik analysmiljö vid återanvändning.
Pre-registrering: Passagerartäthet på Stockholms tunnelbaneplattformar med och utan exponering för blått ljus: En kvasi-experimentell observationsstudie
Keywords: PSYCHOLOGY; PSYKOLOGI; UNDERGROUND RAILWAYS; TUNNELBANOR; SUICIDE; SJÄLVMORD; TRANSPORT ACCIDENTS; TRANSPORTOLYCKOR; Blue Light; Blått ljus; Suicide Prevention; Suicidprevention; PSYCHOLOGY; PSYKOLOGI; Psychology (Excluding Applied Psychology); Psykologi (exklusive tillämpad psykologi)